Analisis Normatif Terhadap Kebijakan Digitalisasi Pelayanan Publik di Tingkat Kecamatan dalam Perspektif Hukum Administrasi Negara - Ansori Ansori; Hairul Umam; Akbar Hidayatullah Vidi Hartono (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the policy of digitizing public services at the sub-district level in the perspective of state administrative law. Digital transformation in the public bureaucracy in the modern era is an important step in creating effective, efficient, and accountable services. However, the implementation of digitalization is often not accompanied by an adequate legal framework, resulting in the potential for administrative irregularities and violations of the principles of good governance. Using a normative research approach, this study examines the compatibility of digitization policies with the principles of state administrative law, such as the principles of legality, legal certainty, proportionality, professionalism, openness, and accountability. The results of this study show that the digitization of public services at the sub-district level requires strengthening technical regulations, increasing the capacity of the apparatus, and integrating digital service systems and standards based on legal principles. This research not only focuses on technological innovation, but is also supported by a strong legal foundation to ensure the protection of public rights and the legitimacy of public services.